2014
DOI: 10.1016/j.ejogrb.2014.05.003
|View full text |Cite
|
Sign up to set email alerts
|

The evaluation of pre and post processing semen analysis parameters at the time of intrauterine insemination in couples diagnosed with male factor infertility and pregnancy rates based on stimulation agent. A retrospective cohort study

Abstract: Objective To identify pre or post processing semen analysis parameters that may be predictive of successful pregnancy in couples with male factor infertility undergoing intra uterine insemination (IUI). To evaluate the pregnancy rate based on ovulation inducing agent in couples with male factor infertility per the 2010 world health organization criteria treated with IUI. Study Design This retrospective study was performed at Stanford University medical center. All couples with male factor infertility fitting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
35
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 13 publications
2
35
2
2
Order By: Relevance
“…Some investigators have suggested a beneficial effect, whereas others observed no benefit . In some cases, the protocols of ovarian stimulation were clearly defined, but in others, different protocols were grouped together . In our study when all ovarian stimulation protocols were lumped together, we could not find any difference in pregnancy or live birth rate.…”
Section: Discussioncontrasting
confidence: 69%
See 2 more Smart Citations
“…Some investigators have suggested a beneficial effect, whereas others observed no benefit . In some cases, the protocols of ovarian stimulation were clearly defined, but in others, different protocols were grouped together . In our study when all ovarian stimulation protocols were lumped together, we could not find any difference in pregnancy or live birth rate.…”
Section: Discussioncontrasting
confidence: 69%
“…11 In some cases, the protocols of ovarian stimulation were clearly defined, 12,15 but in others, different protocols were grouped together. 13,14 In our study when all ovarian stimulation protocols were lumped together, we could not find any difference in pregnancy or live birth rate. The same applied to our case series if we grouped all cases of ovarian stimulation together, in which case the live birth and pregnancy rates were 7 and 9.5% compared with no stimulation, for which the corresponding rates were 7.6 and 9.3% (P = 0.39 and 0.77, respectively).…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…There is only one accepted male semen analysis parameter, either from the pre or post processing analysis, which has been shown to be predictive of IUI outcome. That parameter total motile sperm count [2]. Data from the literature are contradictory and do not allow to identify clearly if other sperm parameters before or after semen treatment are associated with IUI success and which minimum threshold values should be accepted to use in daily practice in order to be able to establish a real guide of good practices for insemination [3].…”
Section: Introductionmentioning
confidence: 99%
“…This study identifies that the total dose of gonadotropin is positively correlated with the pregnancy rate. Moreover, other factors contributing to failure or success of IUI outcome according to this study's findings include semen volume, male age, sperm normal and amorphous morphology, duration of the marriage, and endometrial thickness which some of them have been considered as the influential attributes in some previous similar studies [42][43][44].…”
Section: Discussionmentioning
confidence: 85%